Characterization of the bovine pseudoautosomal boundary: Documenting the evolutionary history of mammalian sex chromosomes - Van Laere, Anne-Sophie; Coppieters, Wouter; Georges, Michel (Genome Research, 2008)
Here, we report the sequence characterization of the bovine pseudoautosomal boundary (PAB) and its neighborhood. We demonstrate that it maps to the 5′ end of the GPR143 gene, which has concomitantly lost upstream noncoding exons on the Y chromosome. We show that the bovine PAB was created ∼20.7 million years ago by illegitimate intrachromatid recombination between inverted, ruminant-specific Bov-tA repeats. Accordingly, we demonstrate that cattle share their PAB with all other examined ruminants including sheep, but not with cetaceans or more distantly related mammals. We provide evidence that, since its creation, the ancestral ruminant PAB has been displaced by attrition, which occurs at variable rates in different species, and that it is capable of retreat by attrition erasure. We have estimated the ratio of male to female mutation rates in the Bovidae family as ∼1.7, and we provide evidence that the mutation rate is higher in the recombining pseudoautosomal region than in the adjacent, nonrecombining gonosome-specific sequences.